2021
DOI: 10.1016/j.ijcard.2021.01.066
|View full text |Cite
|
Sign up to set email alerts
|

Standard and emerging CMR methods for mitral regurgitation quantification

Abstract: Background: There are several methods to quantify mitral regurgitation (MR) by cardiovascular magnetic resonance (CMR). The interoperability of these methods and their reproducibility remains undetermined. Objective: To determine the agreement and reproducibility of different MR quantification methods by CMR across all aetiologies. Methods: Thirty-five patients with MR were recruited (primary MR = 12, secondary MR = 10 and MVR = 13). Patients underwent CMR, including cines and four-dimensional flow (4D flow). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…The present study data demonstrated that 4DF indirect is highly reproducible with higher concordance to standard CMR than 4DF direct . Recently, Fidock and colleagues [ 16 ] reported similar findings for primary MR. Nevertheless, they analyzed a small subgroup (n = 12), provided no direct comparison with TTE, and reported a rather low RVol (mean 28.6 ± 2.5 ml).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The present study data demonstrated that 4DF indirect is highly reproducible with higher concordance to standard CMR than 4DF direct . Recently, Fidock and colleagues [ 16 ] reported similar findings for primary MR. Nevertheless, they analyzed a small subgroup (n = 12), provided no direct comparison with TTE, and reported a rather low RVol (mean 28.6 ± 2.5 ml).…”
Section: Discussionmentioning
confidence: 57%
“…Recently 4D flow CMR was introduced and validated in vitro with phantom models [ 11 ], and first clinical experiences with healthy subjects and patients with MR demonstrated its feasibility. However, previous studies have been performed in functional MR [ 7 , 8 ], congenital heart disease [ 8 , 15 ], small study groups [ 10 , 16 ], or in rather mixed patient populations [ 9 , 11 , 12 , 16 ]. In the present study we investigated the clinical utility of 4D flow CMR in a homogeneous group of MVP patients.…”
Section: Discussionmentioning
confidence: 99%
“…It allows the visualization of flow in multiple orientations to follow the spatial motion of the heart valves and the variable direction of the jets over time. The use of such a retrospective tracking method in a single volume acquisition covering the entire heart may enable direct MR jet volume quantification, overcoming certain limitations of 2D sequences ( 25 ). Recent reports have demonstrated its feasibility in mild to severe MR ( 26 ).…”
Section: Mitral Regurgitationmentioning
confidence: 99%
“…Recent reports have demonstrated its feasibility in mild to severe MR ( 26 ). However, its accuracy has usually been poor in comparison to 2D flow, especially in primary MR ( 25 ). This promising technique, which is constantly improving, is not yet commercially available for all scanners.…”
Section: Mitral Regurgitationmentioning
confidence: 99%
“…Recently, four-dimensional (4D) flow CMR has emerged as an innovative imaging technique to quantitate MR based on a three-dimensional and time-resolved assessment of blood flow MR ( 102 ). Both in patients with primary MR and specifically in patients with MVP, quantification of mitral regurgitant volume has shown to be reproducible and feasible using 4D flow CMR ( 103 , 104 ). However, this technique requires additional acquisition and post-processing time and future studies are needed to evaluate a potential clinical outcome benefit over the indirect 2D CMR technique ( 102 ).…”
Section: Assessment Of Mitral Valve Prolapse Mitral Regurgitation Sev...mentioning
confidence: 99%